Climate change and human behaviour : Understanding modal choice in a rapidly urbanising Arctic - Chapman, David; Larsson, Agneta (Luleå tekniska universitet, Arkitektur och vatten, 2020)
This research explores the human dimension of non-motorised transport, i.e. soft-mobility in Arctic communities. Empirical results are used to show how people’s modal choice in the European Arctic is being influenced by climate evolution and human-made climate change. From these results, it is possible to conceive new visions of the how to design the outside environments of Arctic settlements that can better enable people to move around in Arctic communities with reduced reliance on vehicles. At the societal level, this research will help reduce energy consumption and pollution from transport. For the individual, it highlights social, economic and the health benefits of soft-mobility. This includes creating places that are attractive, safe, and recognisable, as a basis for people’s informed decision-making about outdoor activities and modal choice. Pilot projects are ongoing in Riksgränsen, Björkliden and Abisko (Sweden) with data collected from residents and tourists using citizen science. Outcomes have practical and policy implications for town planning and tourism.